Magma-driven hydraulic fracturing and infiltration of fluids into the damaged host rock, an example from Dronning Maud Land, Antarctica - Engvik, Ane K.; Bertram, Andreas; Kalthoff, Jörg F.; Stöckhert, Bernhard; Austrheim, Håkon; Elvevold, Synnøve (Journal of Structural Geology, 2005)
Excellent outcrops in Dronning Maud Land, Antarctica, provide unique insight into the mode and extent of fluid infiltration into metamorphic and plutonic rocks in the middle crust. The fluids are liberated from pegmatitic veins and give rise to alteration halos. In the alteration halos, the conspicuous change in colour is correlated with (1) hydration mineral reactions, and (2) high density of microcracks in quartz and feldspar exceeding that observed in the unaltered host rock by an order of magnitude. The field relations indicate that the veins originated as melt-driven hydraulic fractures, sealed by pegmatite and aplite crystallising from volatile-rich melts, with the alteration halo being the wake of the process zone formed at the tip of the propagating fractures. It is proposed that (1) the size of the alteration zone and the width of the vein are correlated, resulting in higher values of both these quantities for cracks propagating at higher velocities and consequently higher crack propagation toughnesses; (2) the damage zone is characterised by a transient state of high permeability which was short-lived due to rapid healing and sealing of microcracks; (3) the infiltration and retrogression of the high-grade rocks can be considered as a quasi-instantaneous process on geologic time scales with a duration of hours to weeks.
Keywords: Dronning Maud Land; geologi; petrologi

Pan-African extension and near-isothermal exhumation of a granulite facies terrain, Dronning Maud Land, Antarctica - Engvik, Ane K.; Elvevold, Synnøve (Geological Magazine, 2004)
The Mühlig-Hofmann- and Filchnerfjella in central Dronning Maud Land, Antarctica, consist of series of granitoid igneous rocks emplaced in granulite and upper amphibolite facies metamorphic rocks. The area has experienced high-temperature metamorphism followed by near-isothermal decompression, partial crustal melting, voluminous magmatism and extensional exhumation during the later phase of the late Neoproterozoic to Cambrian Pan-African event. Remnants of kyanite–garnet–ferritschermakite–rutile assemblages indicate an early higher-pressure metamorphism and crustal overthickening. The gneisses experienced peak granulite facies temperatures of 800–900 °C at intermediate pressures. Breakdown of garnet + sillimanite + spinel-bearing assemblages to cordierite shows subsequent re-equilibration to lower pressures. An E–W foliation dominating the gneisses illustrates transposition of migmatites and leucocratic melts which evolved during the near-isothermal decompression. Occurrence of extensional shear bands and shear zones evolving from the ductile partial melting stage through semiductile towards brittle conditions, shows that the uplift persisted towards brittle crustal conditions under tectonic W/SW-vergent extension. Late-orogenic Pan-African quartz syenites intruded after formation of the main gneiss fabric contain narrow semiductile to brittle shear zones, illustrating that the extensional exhumation continued also after their emplacement. The latest record of the Pan-African event is late-magmatic fluid infiltration around 350–400 °C and 2 kbar. At this stage the Pan-African crust had undergone 15–20 km exhumation from the peak granulite facies conditions. We conclude that the later phase of the Pan-African event in central Dronning Maud Land is characterized by a near-isothermal decompression P–T path and extensional structures indicating tectonic exhumation, which is most likely related to a late-orogenic collapsing phase of the Pan-African orogen.
Keywords: Dronning Maud Land; geologi; petrologi

A geochronological and geochemical study of rocks from Gjelsvikfjella, Dronning Maud Land, Antarctica—implications for Mesoproterozoic correlations and assembly of Gondwana - Paulsson, Oskar; Austrheim, Håkon (Precambrian Research, 2003)
The Jutulsessen nunataks (72°00′S; 2°30′E), Gjelsvikfjella, Dronning Maud Land (DML), consist mainly of migmatites of two types. A heterogeneous banded amphibolite facies gneisses and a more homogeneous part. In the more homogeneous part, partial melts form along axial planes to tight folds. Numerous pegmatitic dykes occur in both migmatites. The homogeneous part of the migmatite has a granodiorite composition. It displays the depletion of Nb–Ta typical for rocks from destructive plate margins and a strongly fractionated REE pattern, specially in LREE (La/Lu ratios varying between 500 and 800). SIMS dating of zircon from the homogeneous migmatite and two pegmatite dykes resulted in two age groups. A concordant age of 1163±6 Ma is calculated from zircon crystals with no rim/core structure and from cores from structurally complex crystals. This age represents the age of the protolith of the migmatite. A Cambrian age of 504±6 Ma is obtained from zircon rims and from sector-zoned zircons. This age represent the time of migmatisation. Sm–Nd depleted mantle model ages range from 1390 to 1770 Ma and suggest that the protolith to the migmatites contained components of older crust (pre-1163 Ma). An igneous complex consisting of a syenite plug (Stabben syenite), gabbroic rocks and aplitic dykes intrudes the metamorphic complex. The syenite and the aplitic dykes are neither deformed nor migmatised or penetrated by pegmatitic dykes. These rocks have elevated LREE and LILE concentrations with an La/Lu ratio of 450 and an Nb–Ta trough. The gabbroic rocks range in composition from melagabbro to monzogabbro and host numerous pegmatitic dykes. SIMS zircon U–Pb data from the Stabben syenite give an age of 500±8 Ma. This age is regarded as the intrusive age of the Stabben syenite. By the single zircon–Pb evaporation method an age of 495±14 Ma is obtained from the aplitic dykes. Sm–Nd depleted mantle model ages between 1800 and 2220 Ma indicate that the dykes formed from a Paleoproterozoic source. A Mesoproterozoic volcanic arc setting of DML and a correlation with the Natal Province, as suggested by several authors, is supported by data in this study. The studied area has consequently been a part of the Kaapvaal/Kalahari craton since Mesoproterozoic time. The Cambrian migmatisation and the intrusions are interpreted as a result of post-collision activity related to the collision between the Kalahari craton and the combined block of Antarctica and Australia during the final assembly of Gondwana. This collision is suggested to be included in the Kuunga Orogeny introduced by Meerat and Van der Voo [J. Geodynam. 23 (1997) 223].
Keywords: Dronning Maud Land; NARE 1989/90; geokjemi; geokronologi; geologi; nunataker; petrologi

Flood Basalts of Vestfjella: Jurassic Magmatism Across an Archaean–Proterozoic Lithospheric Boundary in Dronning Maud Land, Antarctica - Luttinen, Arto V.; Furnes, Harald (Journal of Petrology, 2000)
Continental flood basalts (CFBs) of Jurassic age make up the Vestfjella mountains of western Dronning Maud Land and demonstrate an Antarctic extension of the Karoo large igneous province. A detailed geochemical study of the 120-km-long Vestfjella range shows the CFB suite to consist mainly of three intercalated basaltic rock types designated CT1, CT2 and CT3 (chemical types 1, 2 and 3) that exhibit different incompatible trace element ratios. CT1 and CT2 of north Vestfjella record wide ranges of Nd and Sr isotopic compositions with initial εNd and εSr ranging from +7·6 to −16·0 and −16 to +65, respectively. The southern Vestfjella is dominated by CT3 with near-chondritic εNd (+2·0 to −4·1) and εSr (−11 to +19). A volumetrically minor suite of ocean island basalt (OIB-)like CT4 dykes (εNd +3·6, εSr +1) cuts the lava sequence in north Vestfjella. The pronounced isotopic differences suggest different magmatic plumbing systems for the heterogeneous CT1 and CT2 suites and the relatively homogeneous CT3 lavas. This is further supported by the palaeoflow directions, which point to major source regions to the north (CT1 and CT2) and east (CT3) of Vestfjella. These source regions can be associated with two contemporaneous major lithospheric thinning zones that permitted magma emplacement and controlled the melting of upper-mantle sources in the Jurassic Dronning Maud Land. The CT1 and CT2 magmas utilized the northern zone of thinning and were emplaced into the 3 Ga Grunehogna craton, whereas the CT3 magmas were emplaced through thinned Proterozoic Maud Belt lithosphere. Trace element and isotopic studies of the identified magma types reveal a complex history of fractionation and contamination at different lithospheric levels. All extrusive rock types show evidence of crustal contamination but this had rather small impact on their diagnostic trace element ratios. Much stronger overprint, in the CT1 and CT2 suites, resulted from contamination with veined Archaean lithospheric mantle, which produced wide ranges of isotopic and highly incompatible element ratios. CT3, in turn, does not show evidence of interaction with the Proterozoic lithospheric mantle. The high-εNd endmembers of CT1, CT2 and CT3 probably closely resemble uncontaminated mantle-derived magmas and indicate three different mantle sources. The CT2 primary magmas were derived from light rare earth element (LREE)-depleted, slightly large ion lithophile element (LILE)-enriched sources, whereas data on the volumetrically preponderant CT1 and CT3 point to variably LREE-enriched, strongly LILE-enriched sources. The sources of CT1, CT2 and CT3 may record large-scale lateral heterogeneity generated by subduction-contamination of the Gondwanan upper mantle. The OIB-like CT4 dykes probably reflect asthenospheric heterogeneities that were unrelated to the proposed subduction-contamination.
Keywords: Dronning Maud Land; geokjemi; geologi; petrografi; petrologi

Petrogenesis of the volcanic suite of Bouvetøya (Bouvet Island), South Atlantic - Prestvik, Tore; Goldberg, Steven; Goles, Gordon G. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1999)
Whole rock and mineral compositions of volcanic rocks collected during the Norwegian Polarsirkel expedition (1978/79) to the volcanic istand of Bovetøya (close to the Bouvet Triple Junction) are discussed and compared with previously published data from the island. The rock types, hawaiite, benmoreite, and peralkaline trachyte and rhyolite (comendite) are related to each other by crystal fractionation processes. The trace element and radiogenic isotope signatures displayed by the Bouvetøya rocks are those of a moderately enriched oceanic island suite. On several isotope plots Bouvetøya rocks fall on or close to mixing lines between the euriched EM-l and HIMU mantle components. Mixing between depleted morb mantle (DMM) and euriched components is not likely. Thus, Bouvetøya displays a typical plume signature.
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1978/79; geokjemi; geologi; petrologi

The geology and age of Peter I Øy, Antarctica - Prestvik, Tore; Duncan, Robert A (Polar Research, 1991)
The island Peter I Oy is located in the Bellinghausen Sea 400 km off the coast of West Antarctica. It is situated at the transition between oceanic and contintental crust close to a former transform fault, the Tharp fracture zone. The island is completely volcanic, consisting of predominantly alkali basalt and hawaiite and some more evolved rocks. Sampling done by the Aurora expedition in 1987 has made dating and detailed petrological studies possible. The island appears to be much younger (< 0.5 Ma) than previously believed. However, the volcanic activity responsible for this oceanic island may have lasted for 10-20 Ma. Volcanic activity at the island thus took place at the same time as post-subduction rift-related volcanism took place along the Antarctic Peninsula and in Marie Byrd Land. However, the petrologic data indicate that this may be coincidental and that the Peter I Oy activity is independent and related to transtensional rifting along the Tharp fracture zone.
Keywords: Peter I. Øy; geologi; petrologi

Petrology of Peter I Øy (Peter I Island), West Antarctica - Prestvik, Tore; Barnes, Calvin G; Sundvoll, Bjørn; Duncan, Robert A (Journal of volcanology and geothermal research, 1990)
Peter I Øy is located in the Bellinghausen Sea, 400 km NE of Thurston Island, West Antarctica. It is a Pleistocene volcanic island situated adjacent to a former tranform fault on the continental rise of the presently passive margin between the Pacific and Antarctica. New K-Ar age determinations ranging from 0.1 to 0.35 Ma show that the volcanism responsible for this island took place at the same time as post-subduction, rift-related volcanism occurred in the nearby Marie Byrd Land and the Antarctic Peninsula. The rocks of the island are alkalic basalt and hawaiite, benmoreite and trachyte. The basic tocks typically contain phenocrysts of olivine (Fo61–84), diopsidic augite, and plagioclase (ca. An60). Small xenoliths are present and consist of mantle-type spinel lherzolite, cumulate clinopyroxenite and gabbro and felsic inclusions that consist of medium-grained strained quartz, plagioclase, and abundant colorless glass. Chemically, the basic rocks are characterized by rather high MgO (7.8–10.2 wt.%) and TiO2 (3.1–3.7 wt.%) and relatively low CaO (8.4–9.5 wt.%) contents. They have steep REE patterns, [(La/Yb)N = 20] with HREE only 5 x chrondrite. Y and Sc are almost constant at relatively low levels. Compatible trace elements such as Ni and Cr show considerable variation (190–300 and 150–470 ppm, respectively.), whereas V shows only little variation. Sr and Nd isotope ratios vary slightly with 87Sr/86Sr averaging 0.70388 and 143Nd/144Nd 0.512782, both typical for ocean island volcanism. Lead isotope ratios are consistently high in basalts; 206Pb/204Pb = 19.194, 207Pb/204Pb = 15.728 and 208Pb/204Pb = 39.290, whereas benmoreïte is somewhat less radiogenic. Oxygen isotope analyses average ‰ . Incompatible trace elements vary by a factor of 1.5–2.0 within the range of the basic rocks. It is proposed that the incompatible trace-element variations represent different degrees (<10%) of partial melting, and that these melts were later modified by minor ( ‰ ) olivine and spinel fractionation. The very small variation in Y (and Sc) and the very fractionated REE pattern indicate that the source had an Y- and HREE-rich residual phase, most probably garnet. Furthermore, it is suggested that the source was slightly hydrous and that melting took place at 18–20 kbar. Trachyte was derived by multiphase fractionation of ne-normative basalts, and benmoreite from hy-normative parental liquids. The rocks of Peter I Øy are generally of the same type and age as those outcropping in extensional regimes on the nearby continent, and therefore, these occurrences may be related to each other in some way. However, the Peter I Øy rocks are considerably more radiogenic in strontium and less radiogenic in neodymium than the rocks of the Antarctic Peninsula and Marie Byrd Land. Possible explanations are that Peter I Øy represent asthenospheric hot spot activity, or transtensional rifting as subduction ceased.
Keywords: Peter I. Øy; geologi; petrologi

Petrology and geochemistry of Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica - Furnes, Herald; Neumann, Else-Ragnhild; Sundvoll, Bjørn (Lithos, 1982)
Mineral and whole rocks analyses of 12 Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica, are presented, and their genesis discussed. On the basis of major oxides and norms the basalts may be classified as olivine and quartz tholeiites. Plotted in the Plag Cpx (Opx + 4Q) and Ol Plag Q projections, the compositions are most compatible with fractional crystallization of olivine, clinopyroxene and plagioclase from a basalt liquid at very low pressure. The ratios between strongly incompatible elements such as Rb, Cs, Zr, Hf, Ta and Th vary considerably, and petrographic mixing calculations give poor fits with respect to Rb, Cs, Ta, Th and light REE. Initial 87Sr/86 Sr ratios range between 0.70347 and 0.70687, and show no correlation with Rb/Sr or any other SIE ratios. The trace element and Sr isotope data thus do not suggest any simple cogenetic petrogenetic model. It is concluded that the basalt melts most plausibly have been contaminated by, or mixed with anatectic melts of crustal material, rather than reflecting mantle heterogeneity.
Keywords: Dronning Maud Land; geokjemi; geologi; petrologi

Basaltene i Vestfjella og Gondwanalands historie - Furnes, Harald (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geokjemi; geologi; petrologi

The geology and petrology of Bouvetøya, south Atlantic Ocean - Imsland, Pall; Larsen, Jørgen Gutzon; Prestvik, Tore; Sigmond, Ellen M (Lithos, 1977)
Keywords: Bouvetøya; forskning; geologi; petrologi